Considerations on subjects of the educational system - Kurzyna-Chmiel, Danuta (The Opole Studies in Administration and Law, 2019)
The legislator considers the term “educational system” as one of the basic education laws. The legal term (included in the Education Law Act) “the educational system covers” lists its elements. They include, for example, various types of schools, kindergartens, alternative forms of preschool education, children’s holiday homes, centers of education. This system realizes recognized values, principles, as well as certain postulates and guidelines contained in the law. In essence, it is a collection of organizational units, whose activity is regulated by the Education Law Act. The majority of these activities are addressed to pupils. Some elements are also addressed to teachers and serve to develop them. Colleges of Social Service Workers do not fit in with the rest of the educational system.